The Effect of Salam Leaf Ethanol Extract on the Histopathology of Doxorubicin-Induced Rats and its Effectiveness in Protecting the Heart Compared with Positive Control (Vitamin E) - Dewi; Ermi Girsang; Ali Nafiah Nasution; Liena (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2021)
This study aims to determine the effect of bay leaf ethanol extract on the histopathological picture of the kidneys of rats induced by doxorubicin. To determine the administration of bay leaf ethanol extract is more effective in protecting the heart than the positive control (Vitamin E). The bay leaves used were obtained from the Harjosari II Medan Amplas area of Medan city. The independent variable in this study was Salam Leaf Ethanol Extract, while the dependent variable was kidney histopathology. This research was conducted at the Pharmacology and Toxicology Laboratory of the Faculty of Pharmacy, University of North Sumatra. The results showed that the administration of vitamin E together with doxorubicin showed a better renal histopathological picture. Vitamin E as a basic antioxidant is able to reduce the damage caused by doxorubicin which is seen in the absence of widening in the Bowman capsule.